Educational administration : - Lunenburg, Fred C. (Thomson, 2008)
"[This text] provides educators with encyclopedic and pragmatic views relevant to contemporary organizational issues that impact administrators, teachers, students, and staff members. It also provides educational leaders and aspiring educational leaders with pertinent information to base their day-to-day decisions and actions as they encounter leadership challenges within their organization."